DESIGN OF A WEBSITE-BASED CHURCH INFORMATION SYSTEM USING THE AGILE METHOD ( OBJECT: HKBP PERUMNAS BATU ONOM) - Jepri Halomoan Simbolon; Arief Ichwani (RADJA PUBLIKA, 2026)
HKBP Perumnas Batu Onom is a Christian place of worship located on Tusam Raya Street, Perumnas-Batu Onom, Pantoan Maju, Siantar District, Simalungun Regency, North Sumatra. The HKBP Perumnas Batu Onom Church has been established since March 13, 1983, and has conducted numerous service activities and visits. However, the service application mechanism is still done directly at the church, which is considered less effective. Based on this issue, a solution was found by shifting the information dissemination and service mechanism to an online medium using a website. The Agile methodology was employed in designing the website, following the stages of the agile method, with data collected through observation and interviews. It was determined that integrating information dissemination and services into a website-based system provides a solution to the problem. The HKBP Perumnas Batu Onom website was successfully created using the PHP programming language and the Laravel framework. To ensure optimal results, Blackbox Testing was conducted with the congregation and church management of HKBP Perumnas Batu Onom. It was found that the HKBP Perumnas Batu Onom information website facilitates the congregation in obtaining information about worship schedules and church activities, and assists church management in managing congregation data and financial reporting.